Analisis Antosianin dan Aktivitas Antioksidan Kue Apem Komposit Ubi Jalar Ungu dan Jagung Metode pH Diferensial dan DPPHdan DPPH - Sya'roni, Alfina Fauzia; Kurnia, Pramudya; Kisnawaty, Sudrajah Warajati (Nutriology : Jurnal Pangan, Gizi, Kesehatan, 2025)
Oxidative stress indicates an imbalance between free radicals and antioxidants, which can potentially cause health problems. This condition can be prevented through the intake of foods rich in antioxidants, including modifying local foods that use purple sweet potato flour and corn flour in Apem cakes as a composite ingredient for rice flour. The purpose of this study was to determine the effect of purple sweet potato flour and corn flour composites on anthocyanin levels and antioxidant activity in Apem cakes. The research method uses an experiment with a completely randomized design consisting of four types treatment based on the percentage of flour comparison. A: 100% rice flour; B: 15% purple sweet potato flour + 35% corn flour + 50% rice flour; C: 25% purple sweet potato flour + 25% corn flour + 50% rice flour; D: 35% purple sweet potato flour + 15% corn flour + 50% rice flour. Anthocyanin content was tested using the pH differential method, and antioxidant activity was analyzed using the DPPH method. The results of this study showed that there were significant differences in anthocyanin content and antioxidant activity between treatments, with p-values of 0.003 and 0.000, respectively. The conclusion was that the highest anthocyanin content and antioxidant activity were found in Apem Cake treatment D, which was 20.14 ppm and 70.74%.